DAMPAK DISIPLIN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA ASN PADA POLRES SITUBONDO DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Desy Andriyana; Muhammad Yahya Arief; Randika Fandiyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The purpose of this study was to analyze the variable effect of Work Discipline and Leadership on ASN Performance at Situbondo Police Station with Work Motivation as an Intervening Variable by using the Partial Least Square (PLS) Structural equation model. The results of the direct effect hypothesis test were obtained through the Smart PLS 3.0 application. Work discipline has a significant positive effect on work motivation (H1 accepted), leadership has a significant positive effect on work motivation (H2 accepted), work discipline has a significant positive effect on the State Civil Apparatus (ASN) performance (H3 accepted), leadership has a significant positive effect on the State Civil Apparatus (ASN) performance (H4 accepted), work motivation has a significant positive effect on the State Civil Apparatus (ASN) performance (H5 accepted), work discipline has a significant positive effect on the State Civil Apparatus (ASN) performance through work motivation (H6 accepted), and leadership has a positive but insignificant effect on the State Civil Apparatus (ASN) performance through work motivation (H7 rejected).